2014
DOI: 10.1111/are.12505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, tissue distribution and nutritional regulation of a Δ6-fatty acyl desaturase-like enzyme in large yellow croaker (Larimichthys crocea)

Abstract: In this study, the full-length cDNA of a D6-fatty acyl desaturase-like (D6-Fad-like) enzyme was first cloned from large yellow croaker, Larmichthys crocea. The cDNA was 2049 bp, with a 107 bp 5 0 -UTR, a 604 bp 3 0 -UTR, and an ORF of 1338 that specified a protein of 445 amino acids. It contains two membrane-spanning domains, three histidine-rich regions and a cytochrome b 5 domain, which all align perfectly with the same domains located in other recently identified vertebrate D5 and D6 desaturases. Sequence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
4
16
0
Order By: Relevance
“…In the present study, fish fed the lowest dietary DHA/EPA ratio (0.65) showed significantly higher expression of both fads2 and elovl5 . Consistently, the fads2 expression of large yellow croaker also increased with decreasing dietary DHA/EPA [69] and moreover, these results are in agreement with the effect that DHA had on down-regulating fads2 and elovl5 in rainbow trout ( Oncorhynchus mykiss ) [70]. However, the increased expression of fads2 and elovl5 observed in the present study for low DHA/EPA dietary treatments did not resulted in increased enzymatic activity to compensate for lower dietary input.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, fish fed the lowest dietary DHA/EPA ratio (0.65) showed significantly higher expression of both fads2 and elovl5 . Consistently, the fads2 expression of large yellow croaker also increased with decreasing dietary DHA/EPA [69] and moreover, these results are in agreement with the effect that DHA had on down-regulating fads2 and elovl5 in rainbow trout ( Oncorhynchus mykiss ) [70]. However, the increased expression of fads2 and elovl5 observed in the present study for low DHA/EPA dietary treatments did not resulted in increased enzymatic activity to compensate for lower dietary input.…”
Section: Discussionsupporting
confidence: 90%
“…Nutritional regulation of genes encoding desaturases and elongases has been proposed as a possible strategy to enhance the endogenous production on n-3 LC-PUFA and optimise their retention in farmed fish 8, 41, 42 . In general, n-3 LC-PUFA can suppress the transcription of the Elovl4 and Elovl5 encoding genes in fish 1420 . Additionally, previous studies found that LC-PUFA and their metabolites can regulate transcription of lipid metabolism related genes through modulation of transcription factors including, among others, Lxrα and Srebp-1 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, little information was available about the molecular basis of LC‐PUFA biosynthesis in large yellow croaker. Recently, a Δ6‐fad‐like has been successfully cloned from large yellow croaker (Zuo, Mai, Xu, Dong & Ai ). Basic information about Fads and Elovl is not only of high relevance in advancing our understanding of molecular basis of LC‐PUFA biosynthesis and regulation in this fish but also provides possibility for applying transgenic technology in the future (Alimuddin, Yoshizaki, Kiron, Satoh & Takeuchi , ; Alimuddin, Kiron, Satoh, Takeuchi & Yoshizaki ; Kabeya, Takeuchi, Yamamoto, Yazawa, Haga, Satoh & Yoshizaki ).…”
Section: Introductionmentioning
confidence: 99%